1993
DOI: 10.1007/bf03009738
|View full text |Cite
|
Sign up to set email alerts
|

Epidural morphine reduces the riskof postoperative myocardial ischaemia in patients with cardiac risk factors

Abstract: Perioperative myocardial ischaemia is a predictor of postoperative cardiac morbidity (PCM). (17,2 vs 50% P= 0,01), et de tachyarythmies (20,7 vs 50%, P < 0,05

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(39 citation statements)
references
References 42 publications
1
35
0
2
Order By: Relevance
“…Sedation may improve outcome by reducing the stress response and its sequelae to these interventions [1]. However, sedation regimens also have potentially adverse effects which may increase morbidity and prolong the clinical course [2].…”
mentioning
confidence: 99%
“…Sedation may improve outcome by reducing the stress response and its sequelae to these interventions [1]. However, sedation regimens also have potentially adverse effects which may increase morbidity and prolong the clinical course [2].…”
mentioning
confidence: 99%
“…We have shown previously that intracerebroventricular administration of DPDPE increases cardiac tolerance to the arrhythmogenic effects of exogenous epinephrine. 19 In addition, in 1993 Beattie et al 20 established that epidural morphine infusion reduces the postoperative risk of ventricular tachyarrhythmias in patients with cardiac risk factors. In 2010, Ling et al 21 found that intrathecal administration of morphine decreased the IS/AAR ratio in rats with coronary artery occlusion and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…131 It is essential that the dose of neuraxial opioid be reduced with use in older patients. 132 Although some studies indicate that the incidence of pulmonary and cardiovascular comorbidity may be lower with neuraxial morphine than with systemic opioids, [133][134][135][136] the overall benefit is observed only when compared with intermittent IV doses and not when compared with IV infusion of opioids. 124,137,138 Neuraxial opioids are associated with side effects that could affect patients' quality of recovery.…”
Section: Neuraxial Opioidsmentioning
confidence: 99%